2020
DOI: 10.3390/polym12102233
|View full text |Cite
|
Sign up to set email alerts
|

Towards 3D Multi-Layer Scaffolds for Periodontal Tissue Engineering Applications: Addressing Manufacturing and Architectural Challenges

Abstract: Reduced periodontal support, deriving from chronic inflammatory conditions, such as periodontitis, is one of the main causes of tooth loss. The use of dental implants for the replacement of missing teeth has attracted growing interest as a standard procedure in clinical practice. However, adequate bone volume and soft tissue augmentation at the site of the implant are important prerequisites for successful implant positioning as well as proper functional and aesthetic reconstruction of patients. Three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…In the past decade, the evolution of 3D printing and additive manufacturing, especially multi-extrusion 3D printing, have been explored in tissue engineering and have showed potential as a valuable strategy for the development of multi-layer scaffolds [ 24 ]. A recent study by Porta et al fabricated a porous multi-layer polycaprolactone with a Sr-hydroxyapatite scaffold via a single step extrusion process and proved that a multi-layer scaffold had improved biological, mechanical and osteogenic capabilities as compared to neat one-layer scaffolds [ 25 ]. In vitro studies had showed that the presence of ceramics within the polymeric matrix enhanced secretion of bone mineralization-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the evolution of 3D printing and additive manufacturing, especially multi-extrusion 3D printing, have been explored in tissue engineering and have showed potential as a valuable strategy for the development of multi-layer scaffolds [ 24 ]. A recent study by Porta et al fabricated a porous multi-layer polycaprolactone with a Sr-hydroxyapatite scaffold via a single step extrusion process and proved that a multi-layer scaffold had improved biological, mechanical and osteogenic capabilities as compared to neat one-layer scaffolds [ 25 ]. In vitro studies had showed that the presence of ceramics within the polymeric matrix enhanced secretion of bone mineralization-related proteins.…”
Section: Introductionmentioning
confidence: 99%
“… Suitable for patient specific scaffolds. 95 Bottom layer: 20% Sr-nHA (bone component) Upper layer: 10% Sr-nHA (cementum) Starch/PCL (30:70 wt%; SPCL) Periodontal tissue (specially for alveolar bone) Bilayered Solvent casting Wet spinning SPCL solvent casting membrane: suitable obstacle for migration of gingival epithelium into the periodontal defect. SPCL fiber has enough biological, physical and chemical properties also suitable for periodontal tissue engineering.…”
Section: Pcl and Plcl-based Layered Scaffoldsmentioning
confidence: 99%
“…Practical utilization requires faster manufacturing processes that maintain adequate print resolution, surface quality, and mechanical integrity, especially to hold relevance for applications in urgent care. Use of modern multi-extrusion printing systems is swiftly rising in tissue engineering for bone and periodontal structures due to its one-step printing approach, improved speeds, and ability to use versatile material formulations (Porta et al, 2020). Second, variations in part quality can occur due to errors introduced during the digital manipulation of virtual models or during the physical construction process.…”
Section: Challenges In Additive Manufacturingmentioning
confidence: 99%